Programa de autoestima, y rendimiento académico en estudiantes del 5º grado de una escuela pública de la provincia de Moyobamba - 2016 - Diaz Carrasco, Segunda Micaela (2019)
ABSTRACT Principal objective of this research study was to determine the influence of an educational program in self-esteem to improve academic performance in students of the 5th grade of primary education in the educational institution, no. 00974-new CHONTALI-SORITOR, MOYOBAMBA was a descriptive study, with a quasi-experimental design, the sample size was formed by 12 students. The results were processed and recorded in an elaborate database on the worksheet from the IBM Statistics SPSS 24 program, student's T was used to demonstrate the influence of the educational program and the level of significance to improve performance. It had main results according to the test the student "t", was a PV of 0.000 which is lower that the level of significance 0.005 therefore the null hypothesis is rejected and accepted the alternative hypothesis, therefore, the self-esteem program influences significantly the academic performance in students of the 5th grade primary school, according to the test in general courses in AD posttest 33% in A 50% in process 17% in conduct 33% outstanding achievement under conduct process 8% 59%. It had the main conclusions, the overall average of performance in general courses is 16, after applying the educational program, regarding the frequency of average academic performance in expected accomplishment has a 0% frequency in process 8.3% in home the 91.7%.